Results from the 2022 Mexican report card on physical activity for children and adolescents - Argumedo, Gabriela; López y Taylor, Juan Ricardo; Ortiz Brunel, Julissa; Gaytán-González, Alejandro; González-Casanova, Inés; González Villalobos, Martín Francisco; Jáuregui, Alejandra; Jáuregui Ulloa, Edtna; Medina, Catalina; Pacheco Miranda, Yoali Selene; Pérez Rodríguez, Marcela; Retano Pelayo, Ricardo Alejandro; et al. (Frontiers in Public Health, 2024)
Introduction. The Mexican Report Card on Physical Activity for Children and Adolescents aims to assess the prevalence of movement behaviors and opportunities to perform them. Methods. Data on 11 indicators were obtained from national health surveys, census data, government documents, websites, and published studies. Data were compared against established benchmarks, and a grade between 0-10 was assigned to each indicator. Results. For Daily Behaviors, we found 34.5% of Mexican children and adolescents meet Physical Activity recommendations (Grade 3), 48.4% participate in Organized Sports (Grade 5), 35-75.8% engage in Active Play outdoors (Grade 4), 54.1% use Active Transportation (Grade 5), 43.6% spend <2 hours in Sedentary Behavior per day (Grade 4), and 65%-91% meet Sleep recommendations (Grade 7). Girls have lower physical activity levels and sports participation than boys of the same age. For Physical Fitness, we found 56.2-61.8% of children and adolescents have an adequate body mass index for their age (Grade 6). For Sources of Influence, we found 65-67% of parents engage in physical activity or sports in a week (Grade 7), 32.2%-53.3% of basic education schools have a physical education teacher (Grade 6), and 37% of neighborhoods in Mexico have sidewalks with trees (Grade 4). Regarding Government, several policies and programs aimed at improving children physical activity were launched but their impact and allocated implementation budget are unknown (Grade 6). Discussion. Mexican children and adolescents engage in low levels of movement behaviors and have limited opportunities to perform such behaviors. The grades and recommendations provided here should be considered to improve such opportunities.